Pengembangan Kreatifitas Melalui Musik Pada Anak Usia Dini StudiKasus di TK ABA Pringwulung Sleman Yogyakarta - Yulianto .; Nurjannah .; Muhammad zaairul haq (STAINU Purworejo, 2018)
This research talks about developing music creativity in early educational children in ABA kindergarten, Priwulung,Sleman, Yogyakarta. The method in this research is decriptive qualitative research. It goes to field study. The data was taken from interview, observation, and also collecting data that is supported to this research. The result of this research shows that (1) music can develop the children's intellegency on early educational children in Kindergarten ABA Pringwulung (2). Music can develop creativity and imagination for early educational children, sing a song with move part of the body on early educational children, and can explore aptitude that children have in musically context.